Testing the Mediating Role of Work Engagement between Work Environment and Organizational Citizenship Behavior among Generation Z Employees - Indri Guslina; Mohammad Fayruz; Adrian Adha; Giharjo Giharjo (Yayasan Sinergi Kawula Muda, 2026)
This study examines the relationship between work environment, work engagement, and Organizational Citizenship Behavior (OCB) among Generation Z employees in Bekasi, Indonesia. Previous studies generally report that work engagement mediates the relationship between supportive workplace conditions and positive organizational behavior. However, limited evidence explains whether this mechanism operates similarly among Generation Z employees in urban workplaces characterized by digital communication, workplace flexibility, and rapidly changing work expectations. This context provides a meaningful boundary condition for Social Exchange Theory (SET) and Job Demands–Resources (JD-R) Theory into positive workplace behavior. Using a quantitative cross-sectional survey, data were collected from 202 Generation Z employees working in various organizations in Bekasi, Indonesia. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that a supportive work environment positively and significantly influences both work engagement and OCB. However, work engagement does not significantly affect OCB and fails to mediate the relationship between work environment and OCB (β = −0.017, p > 0.05). These findings suggest that supportive workplace conditions directly encourage discretionary organizational behavior without requiring strong psychological attachment to work. Practically, organizations should prioritize supportive work environments, effective communication, teamwork, and collaborative organizational climates to strengthen OCB among Generation Z employees. Because this study focuses on Generation Z employees in Bekasi, the findings should be interpreted within this context. The study contributes to SET and JD-R Theory by demonstrating that work engagement may not always function as a mediating mechanism in explaining OCB among younger digital-oriented employees.